2014
DOI: 10.3945/jn.113.181487
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Absorption by Young Adults from Supplemental Zinc Citrate Is Comparable with That from Zinc Gluconate and Higher than from Zinc Oxide

Abstract: The water-soluble zinc salts gluconate, sulfate, and acetate are commonly used as supplements in tablet or syrup form to prevent zinc deficiency and to treat diarrhea in children in combination with oral rehydration. Zinc citrate is an alternative compound with high zinc content, slightly soluble in water, which has better sensory properties in syrups but no absorption data in humans. We used the double-isotope tracer method with 67Zn and 70Zn to measure zinc absorption from zinc citrate given as supplements c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 24 publications
0
63
0
1
Order By: Relevance
“…Finally, zinc, that has no body reservoirs and is strictly dependant on daily feeding [42], is also necessary because the main enzymes involved (MTHFR, MTRR, CBS) work by means of zinc fingers. It is to be noted that only chelated zinc is actually bio available and that most of the commercial supplements contain zinc oxide that provides a negligible support [43]. The above substances in due amounts have the potential to saturate the 1CC and to generate an excess of activated methyl groups (SAMe) for the activation of CBS and for an efficient GSH output anytime it is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, zinc, that has no body reservoirs and is strictly dependant on daily feeding [42], is also necessary because the main enzymes involved (MTHFR, MTRR, CBS) work by means of zinc fingers. It is to be noted that only chelated zinc is actually bio available and that most of the commercial supplements contain zinc oxide that provides a negligible support [43]. The above substances in due amounts have the potential to saturate the 1CC and to generate an excess of activated methyl groups (SAMe) for the activation of CBS and for an efficient GSH output anytime it is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Several conditions, including growths retardation, hypogonadism, impaired immune system, and neurological dysfunctions, are attributed to Zn deficiency (Maret & Krezel, 2007). Zn deficiency appears to be common in developing countries, particularly in infants, pre-schoolers, pregnant and lactating women, and older adults (Maret & Sandstead, 2006;Wegmüller, Tay, Zeder, Brnić , & Hurrell, 2014). Intestinal Zn absorption depends on the amount of mineral consumed and its bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not known whether dietary zinc intake affects intraprostatic zinc levels, our earlier studies on rats have indicated that oral administration of zinc significantly increases its concentration in the prostate, but its availability in this organ varies based on individual zinc preparations, which may be based on differences in absorption associated with zinc preparations [15]. Wegmüller et al (2014) notes that in humans, zinc gluconate, like citrate, should be recommended for the prevention of zinc deficiency [16]. …”
Section: Introductionmentioning
confidence: 99%